The Influence of Academic Supervision and the Use of the Merdeka Mengajar Platform on the Teaching Quality of High School Teachers in the Rambang Kuang Sub-district - Yulianti, Yulianti; Arafat, Yasir; Rohana, Rohana (Raudhah Publisher, 2024)
This research, conducted under the PGRI Palembang University Education Management Postgraduate Program with Main Supervisor Mr. Assoc. Prof. Dr. Yasir Arafat, S.E., M.M. and Co-supervisor Mrs. Assoc. Prof. Dr. Rohana, M.Pd CIQnR, aims to determine and describe the partial and simultaneous influence of academic supervision and the use of the PMM (Platform Merdeka Mengajar) on the teaching quality of teachers in state high schools in the Rambang Kuang District. The population for this study consisted of all teachers at State High School 1 and State High School 2 in the Rambang Kuang District, totaling 53 teachers, with a total sample size of 53 using the saturated sampling technique. A descriptive analysis method with a quantitative approach was applied, utilizing observation, questionnaires, and documentation for data collection, and data analysis was performed using the t-test and F-test. The findings of the study indicate that: (1) the principal's academic supervision has an influence on the teaching quality of teachers in State High Schools in the Rambang Kuang District; (2) the use of PMM positively impacts the teaching quality of teachers in the district; and (3) a combination of the principal's academic supervision and the use of PMM simultaneously influences the teaching quality of teachers in State High Schools in the Rambang Kuang District by 94.6%, with the remaining 3.4% influenced by other variables not examined in this research.